Narratives of Sustainability: South Asian Literature on Environmental and Social Crises - Masroor, Nida; Ajmal, Muhammad; Khan, Saima Yousaf (Annals of Human and Social Sciences, 2024)
The study aims to investigate the approaches used by South Asian literature to treat the environmental and social conflicts in search of discursive possibilities of sustainability. Many alarming issues are characteristic of South Asia, including environmental pollution and social injustice linked to demographic shifts in such spheres as urbanization and industrialization. As for the research method, this particular learning exercise uses a qualitative approach, it performs a systematic analysis on South Asian literary works with emphasis on environmental and social areas. The study reveals that there are various representations of the themes of environmental pollution, climate change, and social problems in South Asian literature. Strategies on how to utilize literature in the enhancement of awareness, discussion and creating call to action towards sustainable development in South Asia are proposed. It is recommended to raise society’s awareness and improve the effectiveness of addressing regional environmental and social problems.